Long-term field test of temperature gradients on the composite girder of a long-span cable-stayed bridge. Issue 13 (October 2019) - Liu, Jiang; Liu, Yongjian; Jiang, Lei; Zhang, Ning
Bridges are inevitably affected by daily, seasonal and annual air temperature and solar radiation. The thermal effects on bridges, especially for long-span cable-stayed bridges with composite girders, are significant and complicated. The evaluation of temperature distribution has been a primary concern to bridge engineers and researchers. This article presents a more than one-year temperature database of a long-span cable-stayed bridge with a small cantilever length-to-web depth ratio in the composite girder. Uniform temperature, linear temperature difference, thermal curvature, and self-equilibrated thermal stress are considered to imply the characteristics of the temperature distribution in such composite girders. Two profiles (profile 1 and profile 2) for positive vertical temperature gradient and one profile (profile 3) for negative vertical temperature gradient are proposed. The extreme temperature differences with a 100-year return period are determined for each profile with extreme value analysis. Among the three profiles, profile 2 is unique for composite girders with a small cantilever length-to-web depth ratio. Based on parametric studies, profile 2 is revised with the cantilever length-to-web depth ratio for wide applications. Finally, comparisons of vertical temperature gradients are made between the investigated composite girder and the recommendations in Chinese Specification.